The HHV-6B U20 glycoprotein binds ULBP1, masking it from recognition by NKG2D and interfering with natural killer cell activation - Weaver, Grant C.; Schneider, Christine L.; Becerra-Artiles, Aniuska; Clayton, Kiera L.; Hudson, Amy W.; Stern, Lawrence J. (Frontiers in Immunology, 2024)
Herpesvirus 6B (HHV-6B) impedes host immune responses by downregulating class I MHC molecules (MHC-I), hindering antigen presentation to CD8+ T cells. Downregulation of MHC-I disengages inhibitory receptors on natural killer (NK) cells, resulting in activation and killing of the target cell if NK cell activating receptors such as NKG2D have engaged stress ligands upregulated on the target cells. Previous work has shown that HHV-6B downregulates three MHC-like stress ligands MICB, ULBP1, and ULBP3, which are recognized by NKG2D. The U20 glycoprotein of the related virus HHV-6A has been implicated in the downregulation of ULBP1, but the precise mechanism remains undetermined. We set out to investigate the role of HHV-6B U20 in modulating NK cell activity. We used HHV-6 U20 expressed as a recombinant protein or transduced into target cells to investigate binding interactions with NK cell ligands and receptors and to assess effects on NK cell activation. We demonstrate that U20 binds directly to ULBP1 with sub-micromolar affinity. Transduction of U20 decreases NKG2D binding to ULBP1 at the cell surface but does not decrease ULBP1 protein levels, either at the cell surface or in toto. Soluble U20 has the same effect. Transduction of U20 blocks NK cell activation in response to cell-surface ULBP1. These results suggest that U20 interferes with NK cell recognition of HHV-6B infected cells by binding host-cell ULBP1, masking it from recognition by NKG2D, resulting in a decrease in antiviral NK cell activation. This surface masking mechanism proposed here is distinct from that previously put forward for U20 from HHV-6A but similar to one suggested for the m152 immunoevasion from the mouse herpesvirus MCMV, which binds to the ULBP1 homolog RAE1γ. Structural modeling of the U20 – ULBP1 complex using SAXS data to align molecular models derived from machine-learning approaches indicates some similarities to the m152-RAE1γ complex. These results represent an important first step in understanding how HHV-6B modulates NK cell responses to facilitate lifelong infection.